MOBILE MARKETING DAN PERSEPSI KONSUMEN ATAS EKUITAS MEREK - Efendi, A.; Lestari, Baroroh (JURNAL PERSPEKTIF BISNIS, 2013)
The purpose of this research is to investigate the effect of mobile marketing and customer perception on brand equity. This study use purposive sampling technique to collect 60 respondents. Response rate for this research is 89.66%. Results support the hypothesis. Thusit can be concludedthat mobilemarketing influenced brand equity.Â Keyword: SMS Marketing, Partial Least Square